A study on the relationship between spectators behavioral intention and satisfaction, event quality and event identity of mega-events - The 2019 WTA Elite Trophy Zhuhai - Li, S.; Zhou, L.; Liu, G.; Liu, X.; Chen, X. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Purpose - Taking the 2019 WTA ELITE TROPHY ZHUHAI as an example, this study aims to explore the relationship between spectator behavioral intention (BI) and event quality: core quality (CQ) and peripheral quality (PQ), event identity (EI), and satisfaction (SAT) of mega-events. Methods - This study used a convenience sampling method to conduct a questionnaire survey of the on-site audience of the 2019 WTA ELITE TROPHY ZHUHAI, and 355 valid data were collected.The StataMP 17 structural equation model (SEM) was built and estimated (standardized) to compare the path coefficients, significance, and also the fit indices: root mean square error of approximation (RMSEA), standardized mean square residual (SMRM), comparative fit index(CFI), and goodness of fit index (GFI).Hypothesis based on the research model:*a*Hypothesis 1 (H1).EQ will positively influence SAT.*b*Hypothesis 2 (H2).EQ will positively influence EI.*c*Hypothesis 3 (H3).SAT will positively influence BI.*d*Hypothesis 4 (H4).EI will positively influence BI. Results and Findings - The results support all hypotheses, with EQ and SAT (= 0.871, p < 0.001), being positively correlated, and EQ having a positive effect on EI (= 0.559, p < 0.001), supporting H1,H2, respectively. sat on BI (= 0.285, p < 0.001) and EI on BI (= 0.458, p < 0.001) Both were positively correlated, supporting H3,H4, respectively. Spectators of major sporting events perceived that event quality, satisfaction, and event identity all had positive effects on their behavioral intentions. Among them, satisfaction and event identity are direct influences on behavioral intention, while event quality indirectly influences behavioral intention through satisfaction and event identity. Discussion - This study investigates the relationship between spectator behavioral intention and satisfaction, event quality and event identity, thus providing a new understanding and insight into the study of spectator behavioral intention in the fields of sports economics, sports marketing and sports management, which helps to better understand the mechanism of spectator behavioral intention formation of large sports events, so as to more effectively meet the needs of spectators and improve the quality of sports events. This will help to improve the quality of sporting events and the social impact of sporting events. The results of the study can provide reference for sport event organizers to better meet the needs of spectators, enhance the attractiveness of sport events, improve the satisfaction of events, enhance the quality of events, increase the recognition of spectators, and thus improve the market value of sport events.